Purification and characterization of a cephalosporin esterase from Rhodosporidium toruloides. - Politino, M (1997)
A novel cephalosporin esterase (EC 3.1.1.41) from Rhodosporidium toruloides was purified to gel electrophoretic homogeneity. The enzyme is a glycoprotein with a molecular mass of 80 kDa. Upon deglycosylation, several forms of the enzyme were observed with a molecular mass range between 60 and 66 kDa. The isoelectric point of the enzyme is approximately 5.6, with the pH optimum for activity occurring at 6.0. The optimal activity of the enzyme occurred at 25 degrees C, with the enzyme rapidly losing activity at temperatures above 25 degrees C. The enzyme deacetylated a variety of cephalosporin derivatives, including cephalosporin C; the Km for this substrate is 51.8 mM, and the Vmax is 7.9 mumol/min/mg. In addition to cephalosporins, the enzyme hydrolyzed short-chain p-nitrophenyl esters, with the activity decreasing with increasing ester chain length. The enzyme also has the ability to acetylate desacetyl cephalosporins in high yields under mild conditions in the presence of various acetyl donors. A comparison of the physical properties of the esterase with those of other well-characterized cephalosporin esterases indicates that the enzyme is unique in this class.